Population differentiation and behavioural association of the two 'personality' genes DRD4 and SERT in dunnocks (Prunella modularis). Issue 3 (February 2016) - Holtmann, B.; Grosser, S.; Lagisz, M.; Johnson, S. L.; Santos, E. S. A.; Lara, C. E.; Robertson, B. C.; Nakagawa, S.
Abstract: Quantifying the variation in behaviour‐related genes within and between populations provides insight into how evolutionary processes shape consistent behavioural traits (i.e. personality). Deliberate introductions of non‐native species offer opportunities to investigate how such genes differ between native and introduced populations and how polymorphisms in the genes are related to variation in behaviour. Here, we compared the genetic variation of the two 'personality' genes, DRD4 and SERT, between a native (United Kingdom, UK) and an introduced (New Zealand, NZ) population of dunnocks, Prunella modularis . The NZ population showed a significantly lower number of single nucleotide polymorphisms (SNPs) compared to the UK population. Standardized F' st estimates of the personality genes and neutral microsatellites indicate that selection (anthropogenic and natural) probably occurred during and post the introduction event. Notably, the largest genetic differentiation was found in the intronic regions of the genes. In the NZ population, we also examined the association between polymorphisms in DRD4 and SERT and two highly repeatable behavioural traits: flight‐initiation distance and mating status (promiscuous females and cobreeding males). We found 38 significant associations (for different allele effect models) between the two behavioural traits and the studied genes. Further, 22 of the tested associations showed antagonistic allele effects for males and females. Our findings illustrate how introduction events and accompanying ecological changes could influence the genetic diversity of behaviour‐related genes.